Próba zastosowania funkcji dyskryminacyjnej do analizy lokalnego rynku pracy - Witkowska, Aleksandra; Witkowski, Marek (The Use of Discriminating Function for Analysis of the Local Labour Market, 2007)
From statistical point of view, the labour market is very complex. Therefore, it should be featured by many diagnostic variables. That is why in the analysis below, a discriminating function was used to estimate the local/district labour market. All the data needed for this empirical research, which involved years 2002-2004, was obtained by using publications issued by Statistical Office in Poznań. By taking all the results into consideration, it can be said, that the experiment was successful and essentially valid.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (14); 2007; nr 1169, s. 228-235